Peran guru pendidikan agama Islam dalam menanamkan kecerdasan emosional pada anak tunanetra - Uzlifatul Dina; Abd. Madjid (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This study aims to analyze the role of Islamic Religious Education teachers in instilling emotional intelligence and to find out the supporting and inhibiting factors in instilling emotional intelligence. This research used a qualitative approach, conducted at SLB Negeri 1 Bantul. The research subjects were the school principal, one Islamic Religious Education teacher, one homeroom teacher, and two visually impaired students. Data was obtained through data collection techniques of observation, interviews, and documentation. The data was then analyzed through several stages of data reduction, data presentation, and conclusions. The results showed that: (1) The role of the Islamic Religious Education teacher at SLB Negeri 1 Bantul is quite good, this is shown by various efforts and routines such as integrating PAI subjects with emotional intelligence, instilling aspects of the values of congregational prayer, reading iqra', student recitations once a semester, Ramadan Islamic boarding schools, Eid al-Adha and religious competition events. In overcoming the existing problems, the role of the PAI teacher is as an educator, motivator, class manager, evaluator, and to share among teachers regarding the obstacles that occur. (2) The research also resulted in some supporting and inhibiting factors in instilling emotional intelligence. The supporting factors are by providing theory accompanied by practice and the main factors from the environment. While the inhibiting factors come from internal and external. The internal ones come from self-awareness, potential, and condition of the child. Whereas the external ones come from the motivation of the surroundings and the environment